The Study of Addition and Subtraction for Two Digit Numbers in Grade One Between Singapore and Taiwan - Yang, Der-Ching; Chang, Ming-Chen; Sianturi, Iwan Andi (American Journal of Education and Learning, 2017)
This study applied the content analysis method to compare the differences of addition and subtraction for two digit numbers in grade one textbook. The published mathematics textbook of “Nani” in Taiwan and “My Pals Are Here [MPAH]” in Singapore were selected to be compared. They are the most popular elementary mathematics textbooks in each country. The results show that MPAH uses different approaches, including counting on, place value chart and standard written algorithm, to lead students to solve two digit plus one digit questions. The Nani textbook highlights the use of pictorial representation and horizontal algorithm. The MPAH textbook also teach two digits plus two digits after the two digits plus one digit in one chapter. However, The Nani textbook only focuses on two digits plus one digit and the two digits plus two digits will be taught at grade two. In addition, the Nani textbook emphasizes the introduction of special terms, such as summand, addend, sum, minuend, subtrahend, and difference. Yet the MPAH does not introduce these mathematical terms.